Strengthen the Nationalism Values of Senior High School Students in Tasikmalaya Through Vidgram Learning Media Based on the Karang Resik Event - Cici Nurfadillah; Fitri Andri Yani; Ine Nova Ayu; Miftahul Habib Fachrurozi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
This article aims to design a learning media based on the events of Karang Resik as an effort to strengthen the values of nationalism in senior high school students in Tasikmalaya. The method used in this research is descriptive qualitative method, will be obtained from literature studies. Vidgram learning media is a learning media in the form of video that is integrated into Instagram media. The media of this event-based Karang Resik event illustrates the values of unity, freedom and a sense of unity among the Tasikmalaya people, Ciamis, TRI, Hizbullah, Sabilillah in the Karang Resik event. With the strengthen of nationalism values in senior high school students, this media can be a supporting medium for solving the problem of intolerance and conservatism in Tasikmalaya City, as well as being an example for the current condition of Tasikmalaya to create and build unity among all Tasikmalaya communities.